Evaluation of Inguinal Hernia Management in Adult Patients: A Contemporary Review - Sastra Gunawan, Erik (Jurnal KESANS : Kesehatan dan Sains, 2025)
Inguinal hernias are classified into two primary types based on their anatomical pathways: direct and indirect inguinal hernias. A direct hernia occurs when the hernia sac protrudes directly through the inguinal (Hesselbach’s) triangle, which is bordered medially by the rectus abdominis muscle, inferiorly by the inguinal ligament, and laterally by the inferior epigastric vessels. This type of hernia may compromise the posterior wall of the inguinal canal. In contrast, an indirect hernia follows the path of the spermatic cord, entering through the deep inguinal ring and extending outside the boundaries of the inguinal triangle. Understanding the anatomical distinctions between these two types is essential for accurate diagnosis, surgical planning, and effective management.